Berry Size Variation of Vitis vinifera L. cv. Syrah: Morphological Dimensions, Berry Composition and Wine Quality - Melo, M.S.; Schultz, H.R.; Volschenk, C.G.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2016)
Berry size has always been a quality factor in wine production. In this study, Syrah grapes from a single vineyard were classified into different size groups according to diameter: small (< 13 mm), medium (13 < diameter < 14 mm) and large (> 14 mm). Smaller berries were present in the highest and larger berries in the lowest numbers. Size distributions were similar in both seasons (2010/2011 and 2011/2012). Berry physical characteristics (mass, volume and skin area) increased with size, showing the same tendency in both years. Positive correlations between berry mass, volume and skin area were found, whereas these variables were negatively related with berry number/kg grapes. Berry volume was negatively correlated with dry skin weight. Skin surface area/berry volume seems to be an indicator of the “dilution” effect associated with increasing size, as larger berries presented the lowest values. In 2012 the grapes were harvested at a higher soluble solid level than in the previous year; large-sized berries presented the lowest levels in both years. The whole-berry analysis of total anthocyanins showed a decrease in concentration and increase in content per berry, from smaller to larger berries. Small berries and the control (naturally occurring berry size mixture) showed a higher extractability of anthocyanins and phenolic compounds than the medium and large berries. Sensorially, wines from medium berries were more consistent over the two years, scoring higher than the rest. Berry sizes were related to wine style differences, and knowing the population of berry sizes in the vineyard close to harvest would offer a possibility to predict wine styles.